The Auditory Nerve Overlapped Waveform (ANOW) Detects Small Endolymphatic Manipulations That May Go Undetected by Conventional Measurements - Lichtenhan, Jeffery T.; Lee, Choongheon; Dubaybo, Farah; Wenrich, Kaitlyn A.; Wilson, Uzma S. (Frontiers in Neuroscience, 2017)
Electrocochleography (ECochG) has been used to assess Ménière's disease, a pathology associated with endolymphatic hydrops and low-frequency sensorineural hearing loss. However, the current ECochG techniques are limited for use at high-frequencies only (≥1 kHz) and cannot be used to assess and understand the low-frequency sensorineural hearing loss in ears with Ménière's disease. In the current study, we use a relatively new ECochG technique to make measurements that originate from afferent auditory nerve fibers in the apical half of the cochlear spiral to assess effects of endolymphatic hydrops in guinea pig ears. These measurements are made from the Auditory Nerve Overlapped Waveform (ANOW). Hydrops was induced with artificial endolymph injections, iontophoretically applied Ca2+ to endolymph, and exposure to 200 Hz tones. The manipulations used in this study were far smaller than those used in previous investigations on hydrops. In response to all hydropic manipulations, ANOW amplitude to moderate level stimuli was markedly reduced but conventional ECochG measurements of compound action potential thresholds were unaffected (i.e., a less than 2 dB threshold shift). Given the origin of the ANOW, changes in ANOW amplitude likely reflect acute volume disturbances accumulate in the distensible cochlear apex. These results suggest that the ANOW could be used to advance our ability to identify initial stages of dysfunction in ears with Ménière's disease before the pathology progresses to an extent that can be detected with conventional measures.